Buckling of externally pressurized corroded spherical shells with wall-thickness reduction in local region. (December 2020) - Zhu, Yongmei; Zhang, Jianfei; Yu, Jiafu; Zhou, Xiang; Zhao, Xilu; Yin, Baoji; Tang, Wenxian
Abstract: This study focused on the buckling of corroded spherical shells with wall-thickness reduction in local regions under a uniform external pressure. For spherical shells whose wall thickness was reduced owing to local corrosion on the outer surface, the effects of the shape, area, depth, and location of the reduction on the buckling properties were evaluated to identify the most dangerous case. Accordingly, the load-carrying capacity of corroded spherical shells with local reduction was predicted. Moreover, by verifying the five buckling prediction formulas of the spherical shells, reasonable prediction formulas for the compressive capacity of the spherical shells under the condition of corrosion defects were obtained. Four scale models were fabricated using resin material for testing. The geometric shape and wall thickness of each spherical shell model were measured and compared with those of the ideal model. Then, the buckling load and ultimate collapse mode were determined through a hydrostatic test. The experimental and numerical analysis results were compared to verify the numerical analysis. Highlights: Proposed a formula for predicting the compressive load of a corroded spherical shell. The effects of the shape, area, depth and location of corrosion thinned on the buckling of the opening spherical shell was discussed. Taking thickness as local corrosion defects, the nonlinear buckling of the opening spherical shells was discussed. The numerical results of thinned spherical shells agree well with experimental results.